PHYSICO-CHEMICAL ANALYSIS OF GINGER OIL EXTRACTION WITH ADSORBED USED COOKING OIL AND ITS UTILIZATION AS TRADITIONAL MASSAGE OIL - Riyanta, Aldi Budi; Amananti, Wilda; Nurbaety, Nurbaety; Aulia, Firda (Agric, 2024)
Used oil is a commodity that can be sought to increase its economic value, one of which is used as an absorber of essential oil from ginger. Ginger has essential oils as anti-inflammatory, but the oil obtained is relatively small and volatile so that it reduces the healing effect. Used oil has the potential to be a massage oil and ginger oil adsorbent to be used to treat inflammation. On the other hand, leaf waste can be converted into activated charcoal which is used as an adsorbent for the treatment process of used oil. The aims of this study was to determine the physicochemical properties of used oil obtained from the extraction process of ginger rhizomes with adsorbed used oil. The method used was the treatment of used cooking oil by adsorbing it using activated charcoal from activated leaf waste. Used cooking oil was then used for solvent extraction of ginger oil content to conduct organoleptic tests, physicochemical properties, inflammatory tests and GC-MS analysis to see the content of the resulting used oil. The results showed that the ratio of ginger to adsorbed used cooking oil with the highest anti-inflammatory effect was at a ratio of 1:1 with good organoleptic results, gingerol content of 11.6%, camphene 3.75% and eucalyptol 6.79 resulting in an antiinflammatory effect close to pure ginger oil of 59.18% with a contact time of 4.55 hours and reaction order 1.